Environmental management systems Understanding organizational drivers and barriers - Tinsley, Stephen; Pillai, Ilona (Routledge, 2006)
The book examines the way in which EMSs are structured to ensure that a company achieves continuous improvement in environmental performance. Alongside practical advice for businesses that wish to achieve accreditation, the book addresses key issues to be aware of to ensure optimum benefits, different strategies that companies may adopt to establish an EMS and the challenges that arise when trying to integrate an EMS into the business strategy. Also included is a review of the ways in which academics try to categorize and predict the effectiveness of these different approaches to EMS using modelling tools. Finally, case studies are presented to demonstrate examples of companies that have implemented their own EMS, the different approaches that they have taken and the resulting issues that have emerged.